Changes in the lease and permanent sale quota markets of a rock lobster fishery in response to stock abundance. (11th January 2015) - León, Rafael; Gardner, Caleb; van Putten, Ingrid; Hartmann, Klaas
Abstract: Effective individual transferable quotas (ITQ) systems rebuild stocks and allow transfer of quotas to more efficient operators. This process requires functional markets for both quota sales and temporary quota leases. These markets are expected to respond to changes in economic rent from the fishery, which is influenced by stock abundance and the international rock lobster price. This research used multistate Markov modelling and Granger causality test to examine changes in the permanent and temporary quota trade in the Tasmanian rock lobster fishery quota market, during periods of both increasing and decreasing stock abundance. The permanent quota trade market was more active during the period of stock growth, while the quota lease market was active in both periods of stock growth and decline. In contrast to theoretical trends in ITQ fisheries, trades in both markets were not linked to the technical efficiency (i.e. catching capability) of operators, but were more driven by the quota owners' financial capacity (i.e. number of owned quotas). Prolonged and unexpected stock decline affected the quota market so that it deviated from the theoretical pattern of ITQ fisheries. Operators previously active in the market reduced their activity, while smaller operators and firms that previously had not traded became more active, so the fleet expanded with smaller operators entering.